House dust mite impairs antiviral response in asthma exacerbation models through its effects on TLR3. Issue 5 (5th February 2018) - Akbarshahi, H.; Menzel, M.; Ramu, S.; Mahmutovic Persson, I.; Bjermer, L.; Uller, L.
Abstract: Background: Impaired antiviral interferon expression may be involved in asthma exacerbations commonly caused by rhinovirus infections. Allergy is a known risk factor for viral‐induced asthma exacerbation, but little is known whether allergens may affect interferon responses. Objective: Our hypothesis is that house dust mite (HDM) impairs viral stimulus‐induced antiviral signalling. Methods: Experimental asthma exacerbations were produced in vitro in human bronchial epithelial cells (HBECs) and in mice using sequential challenges with HDM and a viral infection mimic, Poly(I:C). We examined rhinovirus pattern recognition receptors (PRRs) signalling pathways and potential mechanisms of impaired interferon response. Results: HBECs and mice exposed to HDM prior to Poly(I:C) exhibited a reduced antiviral response compared to Poly(I:C) alone, including reduced IFN‐β, IFN‐λ, TLR3, RIG‐I, MDA5, IRF‐3 and IRF‐7. Heat inactivation of HDM partially restored the TLR3‐induced interferon response in vitro and in vivo. Our HBEC‐data further showed that HDM directly affects TLR3 signalling by targeting the receptor glycosylation level. Conclusions: Direct effects of allergens such as HDM on PRRs can present as potential mechanism for defective antiviral airway responses. Accordingly, therapeutic measures targeting inhibitory effects of allergens on antiviral PRRs may find use as a strategy to boost antiviral response and ameliorate exacerbations in asthmatic patients.